2018
DOI: 10.1111/petr.13285
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of age and genotype‐guided tacrolimus dosing after pediatric solid organ transplantation

Abstract: CYP3A5 genotype-guided dosing stratified by age resulted in earlier attainment of therapeutic tacrolimus concentrations and fewer out-of-range concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…Our findings suggest that it may be of advantage stratifying genotype-guided dosing by the graft size (GRWR) instead of the recipient age 17 . We reported in Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Our findings suggest that it may be of advantage stratifying genotype-guided dosing by the graft size (GRWR) instead of the recipient age 17 . We reported in Fig.…”
Section: Discussionmentioning
confidence: 87%
“…There is compelling evidence that CYP3A5 expressers require a 1.5-to 2-fold higher tacrolimus dose than nonexpressers [15,[17][18][19][30][31][32][33][34][35][36]. A randomized clinical trial of age-and genotype-guided tacrolimus dosing in children concluded that CYP3A5 genotype-guided dosing stratified by age resulted in earlier attainment of therapeutic tacrolimus concentrations and fewer out-of-range concentrations [37]. Clinical outcomes were not studied.…”
Section: Discussionmentioning
confidence: 99%
“…9 A randomized clinical trial in pediatrics showed that CYP3A5 genotypeguided dosing based on age resulted in earlier attainment of target concentrations. 15 There are little to no data in the dosing of sirolimus, an immunosuppressant frequently prescribed off-label in the pediatric population, for infants and newborns. In the last 5 years, clinical pharmacology research has led to the development of population pharmacokinetic models in this young population, and model-informed precision dosing has been used to achieve therapeutic response in children with vascular anomalies.…”
Section: Researchmentioning
confidence: 99%